2015
DOI: 10.1021/acs.energyfuels.5b01236
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Low-Salinity Waterflooding in Secondary and Tertiary Enhanced Oil Recovery in Limestone Reservoirs

Abstract: Improved oil recovery from oil-wet low-permeability limestone reservoirs is a great challenge by altering the reservoir rock wettability. The purpose of this study is to compare the results of low-salinity waterflooding in secondary and tertiary modes to decrease the residual oil saturation from limestone reservoirs. Three different stock-tank crude oils and limestone cores are used in this study. All of the coreflooding experiments were performed at 60 °C and 2000 psi by injection of actual formation and seaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 47 publications
0
36
1
Order By: Relevance
“…Recovery results were compared by flooding Na 2 SO 4 , NaCl, and MgCl 2 brines as secondary mode [18]. They suggested that low salinity brine enriched in (SO 4 2− ) and depleted in monovalent ions is suitable in oil recovery.…”
Section: Ion Tracking From Secondary Flooding By Ls Brinesmentioning
confidence: 99%
“…Recovery results were compared by flooding Na 2 SO 4 , NaCl, and MgCl 2 brines as secondary mode [18]. They suggested that low salinity brine enriched in (SO 4 2− ) and depleted in monovalent ions is suitable in oil recovery.…”
Section: Ion Tracking From Secondary Flooding By Ls Brinesmentioning
confidence: 99%
“…The wettability alteration may occur via various EOR methods such as smart water injection (Gandomkar and Rahimpour 2015;Rivet et al 2010), low-salinity water injection (Tang and Morrow 1997a;Shehata and Nasr El-Din 2015;Samira et al 2018), and Nano EOR (Hendraningrat et al 2013). There exist some conventional experimental methods to investigate the occurrence and contribution of wettability alteration during various EOR techniques such as contact angle measurement (Mahani et al 2015a), flotation test (Anderson 1986), adhesion test (Anderson 1986;Tiab and Donaldson 2004), spontaneous imbibition (Shehata and Nasr El-Din 2015), core-flooding (Wickramathilaka et al 2011), and capillary pressure measurement (Anderson 1986;Shaker Shiran and Skauge 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The recovery from outcrop chalk cores was not affected by low-salinity water, both at ambient and reservoir temperature (Zahid et al 2012). Most of these works indicated that the ion concentration should be changed during low-salinity water injection to wettability alteration that occurs (Shehata and Nasr El-Din 2015;Rivet et al 2010;Gandomkar and Rahimpour 2015); however, various mechanisms have been proposed for this phenomenon (as mentioned above) (Tang and Morrow 1999;McGuire et al 2005b;RezaeiDoust et al 2009;Ligthelm et al 2009;Austad et al 2010;Mahani et al 2015b;Lager et al 2008). In addition, if the low-salinity water injection method is performed as a tertiary oil recovery method, at least a portion of saturated water is diluted as a result of secondary water injection.…”
Section: Introductionmentioning
confidence: 99%
“…Improved recovery during CSW in carbonates appears to be observed when the initial wetting state is mixed- or oil-wet, and the wettability changes to become more water-wet after injecting water with modified composition8912152122242526. As the reservoir first fills with oil, polar functional groups on the molecules in the oil may adsorb onto the mineral surfaces, rendering them oil-wet.…”
mentioning
confidence: 99%